2013
DOI: 10.1614/ws-d-12-00133.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Ascorbate–Glutathione Cycle in Paraquat Tolerance of Rice

Abstract: Out of 1,343 mutant lines of rice mutated by sodium azide from the parental Japonica-type variety ‘Tainung 67’ (TNG67), a paraquat-susceptible line 1192 and a paraquat-tolerant line 72 were selected using whole seedlings at the four-leaf stage and leaf segments at the tillering stage as test materials. Further selection from progenies of these two mutant lines yielded the susceptible 1192-11 (S) and tolerant 72-16 (T), which were studied herein. Chlorophyll fluorescence, electrolyte leakage, and lipid peroxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…A mutant pool of rice variety TNG67 contains more than 3000 mutants with many desirable traits were developed by sodium azide mutagenesis at the Taiwan Agricultural Research Institute [16]. In our previous study, two pure mutant lines, the paraquat tolerant 72 (T, Pq72) and susceptible 1192 (S, Pq1192), have been screened from this mutant pool [17], and the physiological mechanism study on the paraquat tolerance mutants revealed no difference in uptake, translocation, and metabolism of paraquat between T and S lines (C. S. Wang, unpublished data). However, the induction of enzymatic activities for free radical scavenging played a critical role in paraquat tolerance [15].…”
Section: Fuerst and Vaughnmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutant pool of rice variety TNG67 contains more than 3000 mutants with many desirable traits were developed by sodium azide mutagenesis at the Taiwan Agricultural Research Institute [16]. In our previous study, two pure mutant lines, the paraquat tolerant 72 (T, Pq72) and susceptible 1192 (S, Pq1192), have been screened from this mutant pool [17], and the physiological mechanism study on the paraquat tolerance mutants revealed no difference in uptake, translocation, and metabolism of paraquat between T and S lines (C. S. Wang, unpublished data). However, the induction of enzymatic activities for free radical scavenging played a critical role in paraquat tolerance [15].…”
Section: Fuerst and Vaughnmentioning
confidence: 99%
“…81, 802, 875, 948, 1081 and 1192) and 7 tolerant (T) lines (No. 72, 713, 881, 882, 883, 986 and 1067) have been selected from 1343 pure mutants at M7 generation from the mutant pool of TNG67 rice variety [17]. After further identification of paraquat tolerance was conducted for three selfed generations, two most stable pure lines, the tolerant 72 (T, Pq72) and susceptible 1192 (S, Pq1192), were confirmed in the M10 generation and selected as the materials for studying the inheritance of paraquat tolerance.…”
Section: Rice Materialsmentioning
confidence: 99%
“…Studies on Pq mode of action on non-target terrestrial plants are several [3,6,8,[17][18][19]. Recently it was proposed that the non-target organism Arabidopsis thaliana is protected from exposure to 1000 μM Pq by increasing NPQ that dissipates light energy and decreases the efficiency of photochemical reactions of photosynthesis (down-regulation of PSII) via the "waterwater cycle" [3].…”
Section: •−mentioning
confidence: 99%
“…Paraquat is a haloid salt [1] that is widely used as a non-selective herbicide to control weeds throughout the world [2-4]. Paraquat resistance in plant cells is determined by the uptake, efflux, sequestration, detoxification, and catabolism of the reactive oxygen species (ROS) generated by paraquat.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines, including putrescine, spermidine and spermine, are small aliphatic polycations that are classified as growth regulators, although the specific mechanisms have not been well elucidated [9]. Exogenous application of polyamines provides high-level resistance against paraquat toxicity in a range of plant organs [4], such as the roots of intact maize seedlings [10], leaf discs of sunflower [11], and leaves of rice [12]. Endogenous polyamine probably plays a vital role in paraquat resistance in plants.…”
Section: Introductionmentioning
confidence: 99%